Implementation of Community Based Tourism and Inventory of Local Resources Supporting Ecotourism Potential in Way Kalam Tourist Village, KPH Way Pisang - Meyliana Astriyantika; Enggar Dwi Cahyo (Journal of Creative Power and Ambition (JCPA), 2026)
Ecotourism is a pattern of natural area management in which there are responsible tourism activities in encouraging environmental conservation, and are beneficial for the community to improve welfare. The Lampung Provincial Government's belief in optimizing the area with the concept of a tourist village based on very diverse potential conditions such as nature, customs of the surrounding community, cultural uniqueness, and patterns of life that occur in everyday life, even the creative economy sector. Way Kalam Tourist village is a tourist village based on ecotourism in Penengahan District, South Lampung Regency. This location has a main attraction, namely the Way Kalam Waterfall, in 2023 it became a priority location for assistance for the nomination of the Indonesian Tourist village Award (ADWI). This area is administratively under the management of the Lampung Provincial Forestry Service because it is included in the register 3 of the Way Pisang KPH. Based on these conditions, the management of this tourist village is directed entirely at the ecotourism concept. With these various potentials, it is considered necessary to know how the involvement of the local community is and what the potential of local resources is that can support the strengthening and development of the governance of this tourist village. This research was conducted for 6 months from May-November 2024 in Way Kalam Tourist village. The types of data taken are primary data using observation and interviews, then secondary data with literature studies and other supporting materials. This research will look at how to implement community-based tourism and provide updated data related to local resources both as attractions and creative economic potential with local wisdom owned by Way Kalam Tourist village. The hope for the future is to maximize governance and increase interest in visiting the location. In addition, the results of the study can be used as a guide for management models or used as a consideration for compiling packages and marketing patterns.